2017
DOI: 10.1080/14686996.2017.1338495
|View full text |Cite
|
Sign up to set email alerts
|

EDTA-assisted phase conversion synthesis of (Gd0.95RE0.05)PO4 nanowires (RE = Eu, Tb) and investigation of photoluminescence

Abstract: Hexagonal (Gd0.95RE0.05)PO4·nH2O nanowires ~300 nm in length and ~10 nm in diameter have been converted from (Gd0.95RE0.05)2(OH)5NO3·nH2O nanosheets (RE = Eu, Tb) in the presence of monoammonium phosphate (NH4H2PO4) and ethylene diamine tetraacetic acid (EDTA). They were characterized by X-ray diffraction, thermogravimetry, electron microscopy, and Fourier transform infrared and photoluminescence spectroscopies. It is shown that EDTA played an essential role in the morphology development of the nanowires. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
7
1
Order By: Relevance
“…The obtained images are given in Figure . Several studies reported that during the annealing process at 900 °C temperature, when phase transformation occurs, anisotropic nanoparticles of trigonal LnPO 4 tend to deform and sinter badly. ,, This, however, is not true in our case, where virtually identical morphological features of both the as-prepared and annealed aerogel samples were observed. This can be evaluated from Figure .…”
Section: Results and Discussioncontrasting
confidence: 69%
“…The obtained images are given in Figure . Several studies reported that during the annealing process at 900 °C temperature, when phase transformation occurs, anisotropic nanoparticles of trigonal LnPO 4 tend to deform and sinter badly. ,, This, however, is not true in our case, where virtually identical morphological features of both the as-prepared and annealed aerogel samples were observed. This can be evaluated from Figure .…”
Section: Results and Discussioncontrasting
confidence: 69%
“…Figure S3 shows that the lifetime of Tb 3+ increased progressively from 363.445 to 540.526 ns when increasing the doping concentration to 0.5% and then decreased to 470.211 ns up to 0.9%. The former is caused by surface species and the removal of luminescence-quenching defects, whereas the latter is mainly caused by increasing effective refractive index of the glass via vital crystallite . A slight lifetime elongation through increasing the doping concentration was also detected for the Tb 3+ emission.…”
Section: Resultsmentioning
confidence: 93%
“…Eulytite-type orthophosphate M 3 A(PO 4 ) 3 (M = Ca, Sr or Ba; A = La, Gd, Y or Lu) possesses high physical, chemical and structure stabilities [20,21], and may thus serve as an important family of phosphor hosts. It should be noted that many other types of inorganic compounds, such as GdPO 4 orthophosphate [22] and NaLn(WO 4 ) 2 tungstate (Ln = La-Lu, and Y) [23], also draw great interest for phosphor applications. For downconversion (DC) luminescence, You et al [24] prepared Eu 2+ /Mn 2+ co-doped Sr 3 Lu(PO 4 ) 3 by solidstate reaction at 1300°C for 3 h in a CO atmosphere and investigated its luminescence and Eu 2+ -Mn 2+ energy transfer; Liang et al [25] produced Ba 3 La(PO 4 ) 3 :Ln 3+ (Ln = Tb, Eu) phosphors via solid reaction at 1200-1250°C for 5-8 h in a thermal carbon atmosphere for color-tunable luminescence; Xia et al [26] synthesized a series of (Ba,Sr) 3 Lu(PO 4 ) 3 :Eu 2+ phosphors by solid reaction at 1300°C for 4 h under a 10%H 2 -90%N 2 gas mixture, and the blue shift of Eu 2+ emission with increasing Sr/Ba ratio was discussed in detail; Xia et al [27] also synthesized eulytite-type Ba 3 Eu(PO 4 ) 3 and Sr 3 Eu(PO 4 ) 3 compounds via solid reaction at 1250°C for 10 h in air, and systematically compared their crystal structures and photoluminescence; Guo et al [28] [11] and BiPO 4 [29].…”
Section: Introductionmentioning
confidence: 99%